MACROCRYSTALS OF PT-FE ALLOY FROM THE KONDYOR PGE PLACER DEPOSIT, KHABAROVSKIY KRAY, RUSSIA: TRACE-ELEMENT CONTENT, MINERAL INCLUSIONS AND REACTION ASSEMBLAGES - Shcheka G.G.; Lehmann B.; Gierth E.; Gömann K.; Wallianos A. (My University, 2004)
Euhedral macrocrystals of Pt-Fe alloy from the Kondyor PGE placer, Khabarovskiy Kray, eastern Siberia, Russia, have a relatively constant composition of Pt2.4-2.6Fe, tin and antimony contents up to 0.3 wt.%, and an unusually low content of all PGE except Pt. The millimetric crystals contain inclusions of fluorapatite, titanite, phlogopite, magnetite, ilmenite and iron-copper sulfides. The macrocrystals have a complex gold-rich rim, with four groups of gold alloy: tetra-auricupride (the most abundant gold-bearing phase), Au-Ag (98-54 wt.% Au), Au-Ag-Cu-Pd and Au-Pd-Cu alloys. The inner part of the reaction rim hosts a variety of PGE minerals, such as stannides, antimonides and tellurobismuthides of Pd and Pt. Stannides occur as copper-bearing (taimyrite-tatyanaite series) and copper-free compounds (atokite-rustenburgite series). The main antimony mineral is Sn-bearing mertieite-II. Tellurobismuthides are represented by Te-rich sobolevskite and an intermediate member of the moncheite-insizwaite solid-solution series. The reaction rim also hosts several unknown phases, such as Pd7Bi3, Pd3Bi, Bi2O3•3H2O, and a phosphocarbonate of thorium. The coarse crystals occur in eluvial and alluvial placers within the Kondyor massif, a zoned clinopyroxenite-dunite intrusion of Paleozoic or Mesozoic age. The inclusion assemblage suggests that the macrocrystals of Pt- Fe alloy are associated with late apatite - magnetite - phlogopite clinopyroxenite bodies, and possibly formed in a late-magmatic pegmatitic environment. The Pt-Fe alloy crystals have undergone hydrothermal overprint by NaCl-rich solutions bearing gold - silver - palladium - copper, which produced a wide variety of intermetallic compounds as well as Pd-bearing intermetallic phases. The aqueous solutions also had a minor but characteristic bismuth - tin - antimony - tellurium component.
Keywords: ferroan platinum; taimyrite; tatyanaite; atokite; rustenburgite; sobolevskite; moncheite–insizwaite; tetra-auricupride; Alaskan-type pluton; Kondyor; Aldan Shield; Russia